2018
DOI: 10.1097/md.0000000000009594
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary plasmacytoma of the trachea

Abstract: Rationale:Extramedullary plasmacytomas (EMPs) are rare solitary soft tissue tumors characterized by monoclonal proliferation of plasma cells. Most lesions occur in the head and neck, but primary tracheal lesions are very rare.Patient Concerns:In this report, we describe a case of tracheal EMP discovered in a 48-year-old man who presented with a history of progressive dyspnea.Diagnoses:Computed tomography (CT) revealed a well-defined nodular mass in the posterior wall of trachea without signs of invasion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In a case report described by Karakullukcu et al., surgical debulking combined with photodynamic therapy was employed to manage residual EMP tumor resulting in a successful outcome ( 31 ). Another therapeutic approach presented in the available literature involved bronchoscopic electrocautery snare combined with CO2 cryotherapy, followed by RTH for EMP located in the trachea ( 32 ). In the presented case report, a surgical debulking approach was employed because radical resection was not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…In a case report described by Karakullukcu et al., surgical debulking combined with photodynamic therapy was employed to manage residual EMP tumor resulting in a successful outcome ( 31 ). Another therapeutic approach presented in the available literature involved bronchoscopic electrocautery snare combined with CO2 cryotherapy, followed by RTH for EMP located in the trachea ( 32 ). In the presented case report, a surgical debulking approach was employed because radical resection was not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…D’Aguillo et al [18] suggested that aggressive radiotherapy was the most common treatment modality for EMP, and a combination of surgery and radiotherapy led to better survival outcomes. Zhang et al [19] reported a case of a patient with tracheal EMP treated with surgery, followed by adjuvant radiotherapy, which achieved better local control too. We consider that the EMP should follow the principle of individualized treatment, taking into account the location and the size of the lesions.…”
Section: Discussionmentioning
confidence: 99%